Penciptaan Film Animasi 2D Diadaptasi Dari Puisi “Engkau” - Muhamad Hadi Hibatullah; Tanto Harthoko; Agnes Karina Pritha Atmani (Institut Seni Indonesia Yogyakarta, 2017)
Abstract Literary works adapted to the film are familiar to the general public. In response to the problem, the animated film